A dantei Orpheus: egy makrotextuális modell. Források és értelmezés - Draskóczy, Eszter (Antikvitás & Reneszánsz, 2018)
My paper focuses on the influence of an important descent-into-hell narratives of classical literature, the catabasis of Orpheus on Dante’s journey through the other world. Dante, in his own confession, is familiar with the Ovidian myth of the Thracian poet, but he is undoubtedly influenced also by other elaborations and interpretations of the myth. One of the aims of this work is to present and explore these sources. The special feature of Orpheus is that he is both poet and traveller of the underworld, and in this quality he turns out an unique Greek-Roman mythological antecedent of Dante. The other purpose of my analysis is to examine Dante’s attitude with the comparison of Dante’s texts and their possible sources, while taking into consideration the 14th century commentaries to Dante which shed light to the intellectual horizon of the contemporary reader.